2018
DOI: 10.1021/acs.jpcc.8b01821
|View full text |Cite
|
Sign up to set email alerts
|

Water Adsorption on Hydrophilic and Hydrophobic Surfaces of Silicon

Abstract: The isotherm thickness and hydrogen-bonding interactions of water layers adsorbed on hydrophilic and hydrophobic surfaces were quantified and compared. The hydrophilic and hydrophobic surfaces were modeled with an OH-terminated native oxide layer on silicon and a HF-etched silicon terminated with hydrogen, respectively. The silicon substrate allows the use of attenuated total reflection infrared (ATR-IR) spectroscopy for quantitative measurement of adsorbed water without interferences from the gas phase water.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
120
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 79 publications
(140 reference statements)
8
120
0
Order By: Relevance
“…The water contact angle on a highly hydrophilic surface may be as low as nearly zero and rises with the hydrophobicity of the solid surface [39,40]. Qualitatively, water adsorption preferentially occurs on hydrophilic surfaces [41][42][43][44][45][46]. Apart from the amount or thickness of the water layers adsorbed on a surface, the surface chemistry can also alter the configuration of water molecules in the adsorbed layer.…”
Section: Effect Of Surface Wettability On Water Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The water contact angle on a highly hydrophilic surface may be as low as nearly zero and rises with the hydrophobicity of the solid surface [39,40]. Qualitatively, water adsorption preferentially occurs on hydrophilic surfaces [41][42][43][44][45][46]. Apart from the amount or thickness of the water layers adsorbed on a surface, the surface chemistry can also alter the configuration of water molecules in the adsorbed layer.…”
Section: Effect Of Surface Wettability On Water Adsorptionmentioning
confidence: 99%
“…When a surface is hydrophilic, both ordered and liquid-like water structures can coexist as the outermost adsorbed layer [10,47]. In contrast, adsorbed water assumes a more liquid-like structure on hydrophobic surfaces [41]. Using MD simulations, Willard et al [48] reported that water molecules adsorbed on hydrophobic surfaces showed diffusive behavior due to the lack of strong interactions with the surface.…”
Section: Effect Of Surface Wettability On Water Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,10,11 Infrared (IR) spectroscopy has proven an ideal method for studying adsorbed water, both qualitatively and quantitatively, as it is very sensitive to water and its states of hydrogen bonding. 9,12,13,14,15 The (O-H) stretching bands located between 3000 cm -1 and 3800 cm -1 give rich qualitative information as they are strongly affected by the molecule's environment and the structure of water. Several water complexes have been reported that can be distinguished within this region based on IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the photonic crystal effect can further enhance the plasmonic resonance effects, although the enhancement can possibly be reduced in microfluidic devices due to the smaller index contrast between biosilica and fluid. Third, the hydrophilic surface of diatom pores can absorb target molecules in the solution due to Langmuir adsorption isotherm, allowing physical concentration of the analyte and facilitates better mass transport to the sensing area . Quantitative analysis of these three different effects is beyond the scope of this manuscript and will be investigated in our future research.…”
Section: Resultsmentioning
confidence: 99%